A convenient synthesis of oxandrolone through a regioselective Candida antarctica lipase-catalyzed transformation - P. Ferraboschi; D. Colombo; P. Prestileo (Tetrahedron: Asymmetry, 2003)
The use of a regioselective CAL-catalyzed transformation of a suitable intermediate allowed a convenient synthesis of oxandrolone, an anabolic hormone actualy employed to improve the quality of life for patients with HIV-infections